Monocularly deprived cats: binocular tests of cortical cells reveal functional connections from the deprived eye - Freeman, RD (J Neurosci, 1988)
Animals that are deprived of vision in one eye during a vulnerable phase of development lose visual function of the eye. Although this phenomenon has been studied extensively, little is known about the mechanism of disconnection of the deprived eye from visual cortex. One fundamental question is whether input remains from that eye. We have examined the hypothesis that there is functional input from a deprived eye to visual cortex that cannot be observed with standard alternate tests of each eye. We have employed a robust visual stimulation procedure in which large sinusoidal gratings are presented to each eye, as well as to both eyes together, at varying relative phases or retinal disparities. Monocular and binocular stimulation was used to test kittens unilaterally deprived for brief, intermediate, or long periods. A fourth group of kittens was studied as normal controls. Standard methods were used to record from single cells in the striate cortex. After initial qualitative exploration of receptive fields, all testing and analysis were quantitative. As expected, monocular tests revealed that, for most cells, the deprived eye was ineffective, i.e., did not activate the unit. This effect was increasingly pronounced as the length of deprivation was increased. However, binocular tests revealed that a large fraction of these cells (30–40%) was clearly influenced by and therefore functionally connected to the deprived eye. This interaction was phase-selective, or suppressive and not selective for phase. There was no indication that the connections that remained were of a specific type, i.e., excitatory or inhibitory. Therefore, excitation and inhibition appear equally resistant to the effects of monocular deprivation. However, with long-term deprivation, we find minimal evidence of functional input from the deprived eye. We conclude that the effects of monocular deprivation occur over a considerably longer time period than was previously thought.